Sperm Donors in the U.S. and Their Relationships to Offspring - Hertz, Rosanna (Revista de Antropología Social, 2018)
New forms of family are emerging in an era of rapid change in reproductive technologies, particularly technologies that employ donor gametes. Donor anonymity has become more problematic as more countries require all donors to be identity release. The role of the sperm bank donor –whether anonymous or identity release– who has contact with his offspring remains unexplored in sociological research. In the United States donors are asked to choose the kind of donor they want to be: anonymous or identity release. But little is known about how donors make this decision, including how they think about their donation and their imagined offspring, or whether they change their minds. Given how identity matters to parents who use donor sperm and to children who are often eager to know more about their origins, this topic deserves closer attention. Data from several data sources are used to trace the evolving narrative about donors and their genetic offspring. United States donor profile accounts from 2003 and 2017 are used to explore whether donor justifications about anonymity/identity release have changed. In-depth interviews conducted between 2013-2015 with donors who switch their donor status offer a unique opportunity to understand both their rationales and the consequences of their shift for parents and their offspring. This approach makes it possible to understand the newly emerging role of donors in nuclear families.